The Jizyah Concept as the Source of Baitul Maal in Supporting the Country's Economy - Syamsuri Syamsuri; Rohul Akbar; Setiawan bin Lahuri; Imam Kamaluddin; Mohammad Ghozali (Universitas Darusssalam Gontor, 2020)
Jizyah is one of the sources of income of baitul maal. Jizyah is an obligation/compensation for the protection of life, property, worship, and military responsibility. Jizyah is defined as a tax paid by non-Muslims. Baitul maal is an institution that has a duty to manage the property of the state, both in the form of income and state expenditure. The modern baitul maal can be interpreted as a financial minister or Indonesian bank that can perform actions in the field of budget and revenue of the state with a view to influence the economic path. This research aims to know if the concept of jizyah can be a source of baitul maal in supporting the country's economy. Research uses a library approach by using analysis content to analyse both primary and secondary data. Then write it with a descriptive method. As for the results of this study, Indonesia is one of the democratic countries, so it is not able to collect taxes only from the kafir dzimmi (non-Muslim). Therefore Indonesia applies various taxes to the community, such as income tax (PPh), value added tax (VAT), sales tax on luxury goods (Vat BM), stamp duty, land and building tax (PBB), land and building rights acquisition (BPHTB) as state income.